A, Setiadi The Effect Of Mudarabah And Musyarakah Financing On Profitability Through Non-Performing Finance (NPF) As An Intervening Variable In Sharia Commercial Banks - Aldi Setiadi; Meldona Meldona; Nanik Wahyuni (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to determine the impact of the non-performing financing (NPF) and mudharabah variable on profitability (ROA) in the context of banks that follow Islamic law. This type of research involves using quantitative data using the technique of data collection via purposive sampling, which is examined using the Smarpls 3 dataset. The study's main focus is on Sharia Commercial Banks' loan portfolio from 2016 to 2022. This study's analysis method employs the partial least squares (PLS) analysis. The study's findings indicate that investments in mudharabah hurt profitability and are not significant, while investments in musyarakah have a positive impact and are significant. While non-performing financing (NPF) has a negative impact and is significant when it comes to return on assets (ROA), margin financing (MF) has a positive impact and is not significant when it comes to ROA and uses NPF as an intervening variable. Keywords: Easyrabah, Musyarakah, NPF, ROA